Intangible culturalheritage of Uzbekistan - Sh.Karimbekova translate; S.Mallakhanov coordinator of the project (Uzbekistan Ichcap, 2017)
This book published the framework of the joint project ''Central Asia-Ichcap cooperative project: PUBLISHING an ICH Promotional Book'' carried out by the Ichcap, national commission of Uzbekistan for Unesko and Iclcas.